2022
DOI: 10.1590/1517-7076-rmat-2022-0169
|View full text |Cite
|
Sign up to set email alerts
|

Processing of pyrite derived from coal mining waste by density separation technique using lithium heteropolytungstate (LST)

Abstract: Pyrite (FeS 2 ) is one of the main tailings derived from coal mining. When processed, pyrite has several applications with high value-added, in contrast, if improperly discarded, it causes major environmental impacts, like the acid mine drainage. For those reasons, the seeking for beneficiation techniques of Pyrite has been the target of numerous studies. One of the most employed techniques is the separation by density using heavy liquids, like bromoform, as a separation medium. In the present work, we propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(24 reference statements)
0
0
0
Order By: Relevance
“…These are great examples that there is no 'one-size-fits-all' solution and each case needs to be diagnosed in detail before proposing solutions A new approach that has been studied by the ANM and CPRM, as an alternative to the initial Terms of Reference, is the removal of pyrite from coal tailings before their discharged. Several studies have demonstrated the feasibility of treating coal tailings, either to accelerate the oxidation kinetics of pyrite with ozone and hydrogen peroxide, aiming to decontaminate the tailings (Gomes et al 2022), or for separation by density using bromoform, with subsequent leaching with water and acetone (Oliveira 2016) or lithium heteropolytungstate (Ghedin et al 2022).…”
Section: Main Challenges To Be Overcome For Future Rehabilitation And...mentioning
confidence: 99%
“…These are great examples that there is no 'one-size-fits-all' solution and each case needs to be diagnosed in detail before proposing solutions A new approach that has been studied by the ANM and CPRM, as an alternative to the initial Terms of Reference, is the removal of pyrite from coal tailings before their discharged. Several studies have demonstrated the feasibility of treating coal tailings, either to accelerate the oxidation kinetics of pyrite with ozone and hydrogen peroxide, aiming to decontaminate the tailings (Gomes et al 2022), or for separation by density using bromoform, with subsequent leaching with water and acetone (Oliveira 2016) or lithium heteropolytungstate (Ghedin et al 2022).…”
Section: Main Challenges To Be Overcome For Future Rehabilitation And...mentioning
confidence: 99%